PENGARUH BRAND IMAGE TERHADAP MINAT KONSUMEN MOBIL ISUZU (STUDI EVALUASI PENJUALAN MOBIL MEREK ISUZU PHANTER PADA PT. ASTRA INTERNATIONAL TBK. CABANG PEKANBARU) - Alfedri, Rizki; Andri, Seno (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The problem in this study is the decline in sales and sales target has been set arrives. The purpose of this study was to determine and analyze brand image, consumer interest and determine on consumer interest in buying a cars Isuzu Panther PT. Astra International, Tbk Branch Pekanbaru. The research concludes that the brand image of the car Isuzu Panther assessed agree, which means respondents agreed with brand image Isuzu Panther car now adays as a fuel efficient car, car with quality, suitable for all terrain thereby increasing rider confidence and the car is easy to maintain and repair. Consumer interest in the car Isuzu Panther on PT. Astra International, Tbk Branch Pekanbaru assessed interested. Analysis with SPSS showed that the brand have very strong against the interest of consumers to buy car Isuzu Panther on PT. Astra International, Tbk Branch Pekanbaru. Brand image has positif influence on consumer interest, so if ther is an increase into consumer interest to buy a car Isuzu Panther on PT. Astra International, Tbk Branch PekanbaruKey words : brand image, consumer interest, Isuzu Panther